Evaluation of Northwest University, Kano Post-UTME Test Items Using Item Response Theory - Ado Abdu Bichi; Hadiza Hafiz; Samira Abdullahi Bello (Institute of Advanced Engineering and Science, 2016)
High-stakes testing is used for the purposes of providing results that have important consequences. Validity is the cornerstone upon which all measurement systems are built. This study applied the Item Response Theory principles to analyse Northwest University Kano Post-UTME Economics test items. The developed fifty (50) economics test items was administered to a sample of 600 students. The data obtained was analysed using XCALIBRE 4 and SPSS 20v softwares to determine items parameters base on IRT models. Indicate that, the test measure single trait by satisfying the condition of unidimensionality. Similarly, the goodness of fit test revealed that, the two parameter IRT model was more suitable since no misfit item was observed and the test reliability was 0.86. The mean examinee ability was 0.07 (SD=0.94). The mean item difficulty was -0.63(SD=2.54) and mean item discrimination was 0.28 (SD=0.04). 16 (33%) items were identified as “problematic” based on difficulty indices, 35(71%) also failed to meet the set standards on the basis of discrimination parameters. it can be concluded that, using the IRT approach, the NWU Post-UTME items are not stable as far as item difficulty and discrimination indices are concerned. It is recommended that, the Post-UTME items should be made to pass through all process of standardisation and validation; test development and content experts should be involve in developing and validating the test items in order to obtain valid and reliable results which will lead to valid inferences